2021
DOI: 10.1063/5.0049161
|View full text |Cite
|
Sign up to set email alerts
|

Halide perovskite two-terminal analog memristor capable of photo-activated synaptic weight modulation for neuromorphic computing

Abstract: Emulation of biological signal processing, learning and memory functions is essential for the development of artificial learning circuitry. Two terminal artificial synapses are supposed to be more feasible with biological system in terms of energy efficiency and processing. Here, we report on the fabrication of organic–inorganic hybrid perovskite based two-terminal artificial synapse in which the synaptic plasticity is modified by both voltage pulses and light illumination. The device emulates important synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…To investigate further the HRS and LRS stability, we have implemented standard states endurance and retention measurements using ac pulses for both types of samples. [24][25][26][27][28] Figure 7 depicts thousands of HRS to LRS cycling loops indicating the overall high endurance of MemPVCell-1 and -2 devices. For these measurements we have used a large number of ac pulses up to 3x10 3 cycles having pulse amplitude of ±1V and duration of 100ms.…”
Section: Endurance and Retention Characteristics Of Mempvcell Devicesmentioning
confidence: 99%
“…To investigate further the HRS and LRS stability, we have implemented standard states endurance and retention measurements using ac pulses for both types of samples. [24][25][26][27][28] Figure 7 depicts thousands of HRS to LRS cycling loops indicating the overall high endurance of MemPVCell-1 and -2 devices. For these measurements we have used a large number of ac pulses up to 3x10 3 cycles having pulse amplitude of ±1V and duration of 100ms.…”
Section: Endurance and Retention Characteristics Of Mempvcell Devicesmentioning
confidence: 99%
“…They fabricated a two-terminal MIM structure with polycrystalline MAPbI 3 films, which are the most well-known materials in the photovoltage field. After this report, diverse halide perovskite materials, such as MAPbI 3– x Cl x , PEA 2 PbBr 4 , MAPbBr 3 , , FAPbBr 3 , , CsPbBr 3 , PEA 2 MA n –1 Pb n Br 3 n +1 , (Cs 3 Bi 2 I 9 ) 0.4 -(CsPbI 3 ) 0.6 , MA 3 Sb 2 Br 9 , Cs 3 Cu 2 X 5 , Cs 2 AgBiBr 6 , and CsPbI 2 Br, were explored to demonstrate artificial synaptic devices.…”
Section: Artificial Synapses With Halide Perovskitesmentioning
confidence: 99%
“…The typical compositions of halide perovskites are AMX 3 , in which the A site is occupied by a monovalent cation and M is occupied by a divalent metal cation, especially Pb. The representative examples are MAPbX 3 , , CsPbX 3 , and FAPbX 3 . Lead-containing halide perovskites were studied because of their high power conversion efficiency (PCE) in addition to the easy and low-temperature synthesis based on a solution process.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Recently, halide perovskites have been extensively studied due to their various physical properties, such as high carrier mobility, bandgap tunability, long carrier diffusion length, low temperature solution cast processability. [12][13][14][15] Meanwhile, it is always found that 0D nanoparticles or quantum dots (QDs) show superior characteristics over the bulk ones due to the quantum confinement effect and high specific surface area. [16] Yang et al reported the resistive switching phenomenon in hybrid (organic-inorganic) perovskite QDs and polymer composite based flexible memory.…”
mentioning
confidence: 99%